Additive Manufacturing for Occupational Hygiene: A Comprehensive Review of Processes, Emissions, & Exposures - Stefaniak, A.B.; Du Preez, S; Du Plessis, JL (Journal of toxicology and environmental health. Part B, Critical reviews, 2021)
This comprehensive review introduces occupational (industrial) hygienists and toxicologists to the seven basic additive manufacturing (AM) process categories. Forty-six articles were identified that reported real-world measurements for all AM processes, except sheet lamination. Particles released from powder bed fusion (PBF), material jetting (MJ), material extrusion (ME), and directed energy deposition (DED) processes exhibited nanoscale to submicron scale; real-time particle number (mobility sizers, condensation nuclei counters, miniDiSC, electrical diffusion batteries) and surface area monitors (diffusion chargers) were generally sufficient for these processes. Binder jetting (BJ) machines released particles up to 8.5 µm; optical particle sizers (number) and laser scattering photometers (mass) were sufficient for this process. PBF and DED processes (powdered metallic feedstocks) released particles that contained respiratory irritants (chromium, molybdenum), central nervous system toxicants (manganese), and carcinogens (nickel). All process categories, except those that use metallic feedstocks, released organic gases, including (but not limited to), respiratory irritants (toluene, xylenes), asthmagens (methyl methacrylate, styrene), and carcinogens (benzene, formaldehyde, acetaldehyde). Real-time photoionization detectors for total volatile organics provided useful information for processes that utilize polymer feedstock materials. More research is needed to understand 1) facility-, machine-, and feedstock-related factors that influence emissions and exposures, 2) dermal exposure and biological burden, and 3) task-based exposures. Harmonized emissions monitoring and exposure assessment approaches are needed to facilitate inter-comparison of study results. Improved understanding of AM process emissions and exposures is needed for hygienists to ensure appropriate health and safety conditions for workers and for toxicologists to design experimental protocols that accurately mimic real-world exposure conditions. ABBREVIATIONS ABS : acrylonitrile butadiene styrene; ACGIH® TLV® : American Conference of Governmental Industrial Hygienists Threshold Limit Value; ACH : air change per hour; AM : additive manufacturing; ASA : acrylonitrile styrene acrylate; AVP : acetone vapor polishing; BJ : binder jetting; CAM-LEM : computer-aided manufacturing of laminated engineering materials; CNF : carbon nanofiber; CNT : carbon nanotube; CP : co-polyester; CNC : condensation nuclei counter; CVP : chloroform vapor polishing; DED : directed energy deposition; DLP : digital light processing; EBM : electron beam melting; EELS : electron energy loss spectrometry; EDB : electrical diffusion batteries; EDX : energy dispersive x-ray analyzer; ER : emission rate; FDM™ : fused deposition modeling; FFF : fused filament fabrication; IAQ : indoor air quality; LSP : laser scattering photometer; LCD : liquid crystal display; LDSA : lung deposited particle surface area; LOD : limit of detection; LOM : laminated object manufacturing; LOQ : limit of quantitation; MCE : mixed cellulose ester filter; ME : material extrusion; MJ : material jetting; OEL : occupational exposure limit; OPS : optical particle sizer; PBF : powder bed fusion; PBZ : personal breathing zone; PC : polycarbonate; PEEK : poly ether ether ketone; PET : polyethylene terephthalate; PETG : Polyethylene terephthalate glycol; PID : photoionization detector; PLA : polylactic acid; PM 1 : particulate matter with aerodynamic diameter less than 1 µm; PM 2.5 : particulate matter with aerodynamic diameter less than 2.5 µm; PM 10 : particulate matter with aerodynamic diameter less than 10 µm; PSL : plastic sheet lamination; PVA : polyvinyl alcohol; REL : recommended exposure limit; SDL : selective deposition lamination; SDS : safety data sheet; SEM : scanning electron microscopy; SL : sheet lamination; SLA : stereolithography; SLM : selective laser melting; SMPS : scanning mobility particle sizer; SVOC : semi-volatile organic compound; TEM : transmission electron microscopy; TGA : thermal gravimetric analysis; TPU : thermo polyurethane; UAM : ultrasonic additive manufacturing; UC : ultrasonic consolidation; TVOC : total volatile organic compounds; TWA : time-weighted average; VOC : volatile organic compound; VP : vat photopolymerization